2017
DOI: 10.1016/j.apsusc.2017.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Modification of wetting property of Inconel 718 surface by nanosecond laser texturing

Abstract: Topographic and wetting properties of Inconel 718 (IN718) surfaces were modified via nanosecond laser treatment. In order to investigate surface wetting behavior without additional post treatment, three kinds of microstructures were created on IN718 surfaces, including line pattern, grid pattern and spot pattern. From the viewpoint of surface morphology, the results show that laser ablated grooves and debris significantly altered the surface topography as well as surface roughness compared with the nontreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 46 publications
3
59
0
Order By: Relevance
“…However, many previous studies have reported that just after laser ablation, the fresh ablated metal surface was hydrophilic or super-hydrophilic with the presence of micro/nanostructures. When the laser ablated surface was exposed to the ambient air for a relatively long time, the wettability transition from super-hydrophilic to super-hydrophobic could be observed [12][13][14][15][16][17][18][19][20]. Recent research efforts have been directed towards the explanation of the wettability transition mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, many previous studies have reported that just after laser ablation, the fresh ablated metal surface was hydrophilic or super-hydrophilic with the presence of micro/nanostructures. When the laser ablated surface was exposed to the ambient air for a relatively long time, the wettability transition from super-hydrophilic to super-hydrophobic could be observed [12][13][14][15][16][17][18][19][20]. Recent research efforts have been directed towards the explanation of the wettability transition mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, super-hydrophobic surfaces present a water contact angle (WCA) over 150° with the lotus effect (rolling angle (RA) below 10°) or the pinning effect (no RA or RA above 10°) [5][6]. Studies on natural creatures with super-hydrophobic surfaces reveal that the presence of micro/nanostructured surface morphology is the main cause for constructing special surface wettability [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…So far, many different techniques have been proposed to successfully achieve bioinspired super-hydrophobic surface through modifying surface morphology and surface chemical compositions including chemical vapor deposition [13]. sol-gel [14], chemical etching [15], laser surface texturing [8][9][10]16], thermal embossing [17] and electrodeposition [18], etc. However, the first three mentioned techniques are limited due to expensive equipment, tedious chemical treatments and complicated multi-step processing procedures [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The wettability is one of the surface properties which is settled by molecules and the area distributed at the boundary surface of carbon nanomaterials and liquids with a range from nm to um, and alteration of the molecules-area with a surface structure of carbon nanomaterials is efficiently able to affect wettability. As methods for change of wettability, various techniques modifying the surface structure and components have been employed [8][9][10][11]. In this regard, and compared with the surface structure of carbon nanomaterials mentioned above, graphene and CNT are horizontal against the substrate.…”
Section: Introductionmentioning
confidence: 99%